Some immunological parameters and interleukin level associated with Chronic myelogenous leukemia patients in Al Anbar governorate - Mohammed, Aysar Mahmood; Mohammed, Mousa Jasim (Journal of Neonatal Surgery, 2025)
Context: Tumor necrosis factor (TNF)-α and other cytokines play a role in the pathophysiology of chronic myeloid leukemia (CML), however their prognostic importance in these conditions remains unclear. The authors evaluated the correlation between serum cytokine levels and clinical outcomes in individuals with CML in the present study. Methodology: Serum concentrations of TNF-a, interleukin (IL)-1 receptor antagonist, IL-6, IL-5, IL-3, IFN 1a, C3, and C5 were assessed in patients with CML1 or CML2 seeking treatment at Al-Anbar Oncology Center. Univariate and multivariate analyses were conducted to examine relationships with clinical outcomes. Outcomes: Elevated TNF-a levels were associated with diminished performance status, increased leukocyte counts, and heightened cytokine levels. Additionally, a robust positive association was observed between TNF-a, INF-a, IL-1a, IL-6, IL-5, IL-3, C3, and C5 in patients with chronic myeloid leukemia (CML). Conclusions: Elevated serum levels of TNF-a, INF-a, IL-1a, IL-6, IL-5, IL-3, C3, and C5 in CML patients signify the severity of the disease.